Barriers to Household Risk Management : Evidence from India - Townsend, Robert (IMF Working Papers; Working Paper ;, 2012)
Why do many households remain exposed to large exogenous sources of non-systematic income risk? We use a series of randomized field experiments in rural India to test the importance of price and non-price factors in the adoption of an innovative rainfall insurance product. Demand is significantly price sensitive, but widespread take-up would not be achieved even if the product offered a payout ratio comparable to U.S. insurance contracts. We present evidence suggesting that lack of trust, liquidity constraints and limited salience are significant non-price frictions that constrain demand. We suggest contract design improvements to mitigate these frictions.